Impact of HNF4α disrupted expression on hepatocellular carcinoma cells sensitivity to oncogenic pathways inhibitors - A. S. Makarova; O. M. Krivtsova; M. S. Chesnokov; N. I. Lazarevich (Успехи молекулярной онкологии, 2017)
Introduction. Hepatocellular carcinoma (HCC) is characterized by aggressive course, high lethality rate and resistance to current systemic treatment. Analysis of molecular aberrations associated with HCC pathogenesis that control biological properties of HCC allows to evaluate potential efficacy of inhibiting certain oncogenic cascades. The present study is focused on investigation of the impact of reduced expression of the key hepatocyte differentiation regulator, HNF4α, often downregulated in HCC, that influences sensitivity of HCC cells to inhibitors  of the major oncogenic pathways mTOR, CDK4/6-pRb and ROCK.Materials and methods. Changes in cells proliferation and migration caused by HNF4А gene stable knockdown were tested in human HCC cell cultures HepG2 and Huh7 followed by examination of these cellular properties under mTOR (rapamycin), CDK4/6 (PD0332991, palbociclib) and ROCK 1/2 (Y27632) inhibitors treatment. Gene expression levels were estimated by the real-time polymerase chain reaction method (Real-Time PCR).Results. HNF4А gene knockdown alters HepG2 and Huh7 cell migration associated with E-cadherin and N-cadherin expression changes. The HNF4α repression weakens Y27632-induced blockade of HCC cells migration potential. HNF4А gene knockdown causes resistance  of Huh7 cells and increase of HepG2 cells sensitivity to rapamycin and PD0332991 that block cells migration ability.Conclusions. Expression level of HNF4α renders influence on migration of HCC cells and contributes to their sensitivity to mTOR, CDK4/6 and ROCK1/2 inhibitors’ impact on cell migration activity.